Promoting players’ safety and welfare through the sharing of scientific knowledge with sports agents: the new reality of Portuguese rugby sevens - Ferreira, António Miguel da Cruz (2020)
As the authors of the recently published article “Epidemiology of injuries in senior male rugby union sevens: a systematic review”, we would like to share with you its impact on the Portuguese rugby community and our achievements since then. [...]